Extrusion model for the Early Mesozoic intracontinental deformation of South China related to the North and South China collision. (8th June 2020) - Tang, Xian‐Chun; Ji, Chen; Li, Qiu‐Huan; Wu, Ying; Zhang, Kai‐Jun
Abstract : The Early Mesozoic tectonic regime of the South China Block was characterized by strike‐slip movement. The northeastern South China Block dominated by recumbent folding, thrusting, and foreland imbrication. Between the North and South China blocks in southern Qinling, there was dextral transpression, but in the western South China Block, sinistral transpression took place. In central South China, sinistral transtension prevails. In contrast, both the eastern and western South China margins, composed of Precambrian basement, appears to be little deformed. These differences are due to lateral extrusion of the South China Block. Extrusion resulted from (a) an overall southerly compression (the North China Block against the South China Block) and indentation of the rigid North China Block into the weaker South China Block, (b) unconstrained South China southern margin, containing a subduction zone between the Indochina Block and the South China Block, allowing the escaped materials to be consumed, (c) an association of strongly constrained margins of the central Sichuan Craton in the western South China margin and the Southeast China Massif in the eastern South China margin, (d) structural obstacle of the Jiangnan Uplift mainly composed of the Proterozoic metamorphic basement, and (e) a previously thickened, gravitationally unstable, thermally weakened crust of the eastern Yangtze valley. The extrusion deformation began about at the beginning of the Jurassic/the end of the Triassic, and terminated at the end of the Cretaceous.